Dakwah dan Pengembangan Kendali Diri: Upaya Antisipasi Kecenderungan Seks Bebas Remaja - Hajir Tajiri (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2010)
Da’wah in context preventing of freesexual behavior on teenager is something not easy. Da’wah in this context need creative efforts either individual or collective and collaborative of all profesion and government policy. One of suitable approach is cognitive-behavioral, with this approach estimated will able giving solution to teenager problem, especially to increase self control ability as prevention step to freesexual tendency. That is by cognition restructurization or modification and rebuild their behavior.